2016
DOI: 10.3389/fpls.2016.00815
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles as a Potential Iron Fertilizer for Peanut (Arachis hypogaea)

Abstract: Nanomaterials are used in practically every aspect of modern life, including agriculture. The aim of this study was to evaluate the effectiveness of iron oxide nanoparticles (Fe2O3 NPs) as a fertilizer to replace traditional Fe fertilizers, which have various shortcomings. The effects of the Fe2O3 NPs and a chelated-Fe fertilizer (ethylenediaminetetraacetic acid-Fe; EDTA-Fe) fertilizer on the growth and development of peanut (Arachis hypogaea), a crop that is very sensitive to Fe deficiency, were studied in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
243
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(264 citation statements)
references
References 52 publications
14
243
1
6
Order By: Relevance
“…The growth inhibition by salinity stress was reported by Netondo, Onyango, and Beck (). Previous studies on rice, peanut, soya bean and wheat showed that n‐Fe 2 O 3 can improve their growth (Alidoust & Isoda, , ; Ghafari & Razmjoo, ; Rui et al., ). The increased growth and biomass by n‐Fe 2 O 3 seed priming under salinity stress could be due to enhanced photosynthetic rate, photosystem II efficiency, water uptake and decreased membrane damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth inhibition by salinity stress was reported by Netondo, Onyango, and Beck (). Previous studies on rice, peanut, soya bean and wheat showed that n‐Fe 2 O 3 can improve their growth (Alidoust & Isoda, , ; Ghafari & Razmjoo, ; Rui et al., ). The increased growth and biomass by n‐Fe 2 O 3 seed priming under salinity stress could be due to enhanced photosynthetic rate, photosystem II efficiency, water uptake and decreased membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that seed treatment with nanometal oxides can improve seed germination, seedling growth and physiology (Du et al., ). Studies on rice ( Oryza sativa L.), wheat, ( Triticum aestivum L.), peanut ( Arachis hypogaea L.) and soya bean ( Glycine max L.) have shown that foliar or soil application of iron oxide NPs improved the growth and yield (Alidoust & Isoda, , ; Ghafari & Razmjoo, ; Li et al., ; Rui et al., ). In another study, application of iron oxide NPs has increased chlorophyll content, antioxidant enzyme activity (superoxide dismutase, catalase and peroxidase) and decreased malondialdehyde in watermelon ( Citrullus lanatus L.; Li et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rui et al evaluated the effectiveness of iron oxide nanoparticles (IONPs; Fe 2 O 3 NPs) as a fertilizer to replace traditional Fe fertilizers [77]. The effects of the Fe 2 O 3 NPs and a chelated-Fe fertilizer (ethylenediaminetetraacetic acid-Fe; EDTA-Fe) on the growth and development of peanut ( Arachis hypogaea ), a crop that is very sensitive to Fe deficiency, were studied in a pot experiment.…”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
“…Fe 2 O 3 NPs adsorbed onto sandy soil and improved the availability of Fe to the plants. Fe 2 O 3 NPs can replace traditional Fe fertilizers in the cultivation of peanut plants[77] Vigna radiata FeNPs 2–6 nm+0.2% gum, +0.4% gum1 mM Fe 2+ ionsNatural biopolymer gum kondagogu as reducing and capping agent was usedThe radical length and biomass was increased in seeds exposed to Fe NPs in comparison to Fe 2+ ions. The α-amylase activity was increased in the seeds exposed to Fe NPs[78] Spinacea oleracea α-Fe 2 O 3 50 nm100, 150, 200 mg kg −1 of soilExperiments were performed in a solid hydroponic medium consisting of sawdust and coco peat and adequate amounts of waterPositive effects on spinach plant due to uptake of Fe 2 O 3 nanoparticles such as increase in stem and root lengths, biomass production and magnetic properties were observed[19] Lactuca sativa Core–shell NPs Fe/Fe 3 O 4 13/9 nm10, 20 mg L −1 15-days treatment of hydroponically grown lettuceThe nano-Fe/Fe 3 O 4 at 10 and 20 mg L −1 and FeSO 4 ·7H 2 O at 10 mg L −1 did not affect lettuce growth and chlorophyll content[71] Vigna unguiculata <100 nm25, 500 mg L −1 The elements were applied 56 and 72 days after sowing over the leaves, and data was collected after day 85Iron had significant effect on yield, leaf Fe content, stem Mg content, plasma membrane stability, and chlorophyll content, probably as a result of more efficient photosynthesis[79] Glycine max γ-Fe 2 O 3 (IONPS) and citrate coated IONPs 6 nm500, 1000 mg L −1 Plant physiological performance was assessed after foliar and soil IONPs fertilizationIONPs produced a significant positive effect on root elongation.…”
Section: Nanomaterials Based On Essential Metals and Their Use In Agrmentioning
confidence: 99%
“…In particular, it is known that metal oxide nanoparticles, such as copper oxide nanoparticles, exert negative effects on plants [2]. On the other hand, some NPs in suitable concentrations can enhance plant growth and could be used as nanofertilizers in agriculture to increase yields and thus decrease environmental pollution caused by classical fertilizers [3][4][5][6]. The biological effects of individual metals are more or less known, but even though combinations of xenobiotics are common in nature; their combined effects still need to be thoroughly investigated.…”
mentioning
confidence: 99%